Serological Biomarkers of Intestinal Collagen Turnover Identify Early Response to Infliximab Therapy in Patients With Crohn’s Disease - Alexdottir, Marta S.; Bourgonje, Arno R.; Karsdal, Morten A.; Pehrsson, Martin; Loveikyte, Roberta; van Dullemen, Hendrik M.; Visschedijk, Marijn C.; Festen, Eleonora A. M.; Weersma, Rinse K.; Faber, Klaas Nico; Dijkstra, Gerard; Mortensen, Joachim H. (Frontiers in Medicine, 2022)
Background Crohn’s disease (CD) is characterized by excessive protease activity and extracellular matrix (ECM) remodeling. To date, 30–50% of patients experience non-response to anti-TNFα treatment. This study aimed to assess whether serological biomarkers of ECM turnover could monitor or predict response to infliximab (IFX) induction therapy in patients with and without a surgical history. Methods Serum biomarkers of type I (C1M), III (C3M), IV (C4M) and VI (C6Ma3) collagen degradation, type III (PRO-C3) and VI (PRO-C6) collagen formation, basement membrane turnover (PRO-C4), and T-cell activity (C4G), were measured at baseline and week 14, in 63 patients with CD undergoing IFX induction therapy. Patients were stratified according to surgical history. Results C4M was elevated at baseline in responders with a surgical history (n=10) and associated with response at baseline (P<0.05). Additionally, C6Ma3, PRO-C3, and PRO-C6 were elevated at week 14 in responders compared with non-responders (n=8) and could differentiate between the two groups (P<0.05). Two biomarker ratios (C4M/C4G and PRO-C4/C4G) were elevated at week 14 in non-responders (n=5) without a surgical history compared with responders (n=40) and could differentiate between the response groups (P<0.05). Conclusion Baseline levels of a serological biomarker for type IV collagen degradation associated with response to IFX induction therapy, and biomarkers of type III and VI collagen formation may be used to monitor response at the end of induction therapy in patients with a surgical history. Biomarker ratios of type IV collagen turnover demonstrated promising results in monitoring treatment response in patients without a surgical history.